RANCANG BANGUN PROGRAM APLIKASI PENYIMPANAN DOKUMEN BERBASIS DESKTOP STUDI KASUS PADA PT MECOSUPRIN GRAFIA JAKARTA - Rudiyanto Rudiyanto; Jamaludin Jamaludin (STIKOM CKI, 2016)
Advances in technology have Introduced computational and storage of data with ease into a device, the which can store large amounts of digital data. Documents are a source of vital information needed in the industry. Print high-quality documents is no longer a difficult, task for the document. The latest evolution of digital printers has opened up new research opportunities in the field of document and document engineering industries. Information security risk management is one of the ways the organization maintaining the confidentiality, integrity and availability of information resources. Dibutukan document management and supporting the data if it is to maintain the relevance / linkages contents of a document. The problems are the weaknesses (vulnerabilities) that would pose a threat (threats) such as loss of data, corruption of data, theft and interception of critical data. The threat of misuse of insider documents is a common problem in an organization. So that motivates Researchers to devise a mechanism to reduce the risk of the spread of digital document information by addressing the problem of illegal insider or insider threats. With the construction of the document storage application program, is expected to documents that exist in each department can be secured from start to manufacture, Accessing, reading, copying, and document destruction by people who do not include. Sistem have set a document management application in soft copy of the which will be stored into the application file. In designing the application using the method of SDLC (System Development Life Cycle) with the waterfall approach is expected the application can be run According to the needs of the company.Keywords: Program Application, Document Management, Document Storage